2021
DOI: 10.1002/brb3.2018
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity patterns in patients with neovascular glaucoma using amplitude of low‐frequency fluctuations: A functional magnetic resonance imaging study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In addition to the IFG, many studies have also shown that optic diseases are associated with dysfunction in the SFG (Min et al, 2018;Xu et al, 2019;Wang et al, 2021). The SFG occupies one-third of the frontal lobe and is thought to be the main premotor area (Peng et al, 2021). It plays roles in working memory presentation of visual space (Leavitt et al, 2018), and is also related to acute social stress (Chang and Yu, 2019), cognitive control (Tully et al, 2014), and self-consciousness (Hsieh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the IFG, many studies have also shown that optic diseases are associated with dysfunction in the SFG (Min et al, 2018;Xu et al, 2019;Wang et al, 2021). The SFG occupies one-third of the frontal lobe and is thought to be the main premotor area (Peng et al, 2021). It plays roles in working memory presentation of visual space (Leavitt et al, 2018), and is also related to acute social stress (Chang and Yu, 2019), cognitive control (Tully et al, 2014), and self-consciousness (Hsieh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when NVG progresses to stage III, a series of symptoms such as vasoconstriction, peripheral conjunctival adhesions, as well as corneal swelling and congestion, severely damage the patient’s vision. In addition, an increase in intraocular pressure (IOP) is accompanied by severe eye pain ( Peng et al, 2021 ). Thus, NVG patients have difficulty in visual recognition, which may lead to a compensatory increase in ITG activity, including ITG.L.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascular glaucoma (NVG) is a secondary eye disease caused by a variety of ocular and systemic diseases and is closely related to retinal ischemia and hypoxia caused by diseases. Three of the most common causative conditions of NVG are ischemic central retinal vein occlusion (CRVO) (33%), diabetic retinopathy (DR) (33%), and ocular ischemic syndrome (13%) ( Peng et al, 2021 ). Clinically, NVG can manifest as increased intraocular pressure, photophobia, severe eye pain, corneal swelling, and iris erythema, causing irreversible visual impairment and severely affecting the lives of patients worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Structural neuroimaging, including voxel-based morphometry (VBM) and diffusion tensor imaging (DTI), indicates an atrophic optic nerve (ON) and lateral geniculate body (LGN), damaged optic radiation (OR), and a thinning visual cortex in glaucoma patients [ 6 9 ]. Functional magnetic resonance imaging (fMRI) has demonstrated several forms of visual task-related deactivation in glaucoma [ 10 ], including decreased visual functional connectivity (FC) [ 11 ], decreased and/or increased amplitude of low-frequency fluctuations (ALFF) in the cuneus and occipital lobe/inferior temporal gyrus [ 12 14 ], and decreased regional homogeneity (ReHo) in the calcarine area [ 15 ]. In addition, structural and functional studies have indicated alterations in the extravisual system, such as the hippocampus [ 16 ], anterior thalamic radiation, superior longitudinal fascicle [ 17 ], and executive network [ 18 ].…”
Section: Introductionmentioning
confidence: 99%